2021
DOI: 10.1093/jamia/ocab010
|View full text |Cite
|
Sign up to set email alerts
|

Toolkits for implementing and evaluating digital health: A systematic review of rigor and reporting

Abstract: Objective Toolkits are an important knowledge translation strategy for implementing digital health. We studied how toolkits for the implementation and evaluation of digital health were developed, tested, and reported. Materials and Methods We conducted a systematic review of toolkits that had been used, field tested or evaluated in practice, and published in the English language from 2009 to July 2019. We searched several ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Regular monitoring and evaluation of digital health innovations is the first step towards ensuring effective and safe DHI implementation, and several toolkits are available for this purpose 60. In the long term, embedding DHIs within healthcare delivery systems is a promising approach for their sustainabilty,61 and DHIs can effectively support integrated care models for NCDs 62.…”
Section: Discussionmentioning
confidence: 99%
“…Regular monitoring and evaluation of digital health innovations is the first step towards ensuring effective and safe DHI implementation, and several toolkits are available for this purpose 60. In the long term, embedding DHIs within healthcare delivery systems is a promising approach for their sustainabilty,61 and DHIs can effectively support integrated care models for NCDs 62.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a recent study, we did not find published recommendations for procedures to conduct a review of a live website in a systematic manner [ 48 ]. A recent systematic review found that despite there being many published toolkits, very few were evaluated, and the authors concluded that this is an area where greater attention and rigorous methodology are needed [ 20 ]. Although review criteria [ 49 ] and a possible framework (Reach, Effectiveness, Adoption, Implementation, Maintenance) from implementation science [ 50 ] have been proposed as useful avenues for evaluation, they are more appropriate for web-based intervention–based studies on behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a rigorous methodology is needed for both the development and evaluation of websites and eHealth resources. However, a recent systematic review found that although there are many toolkits for digital health, evaluations of these toolkits are uncommon [ 20 ]. This study aims to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…This collaboration of PICT policymakers, government, management, and technical staff has facilitated the co-creation of digital health profiles and a maturity assessment to guide national digital health strategies and roadmaps. [32][33][34][35][36][37] The Asian eHealth Information Network is a similar example involving political, managerial, and technical actors, particularly from countries comprising the Association of South-East Asian Nations. 38…”
Section: European Regionmentioning
confidence: 99%